Digital literation of citizens neighborhood association’s WhatsApp group in response Covid-19 information - Wenerda, Indah (International Journal of Communication and Society, 2022)
This research aims to find out the competence of digital literacy of citizens to infodemic received through WAG neighborhood association 09 Dipowinatan. This research was conducted using qualitative interpretative research with research method of netgraph analysis. The data collection method used in this study was participant observation at the Dipowinatan neighborhood association on WAG. Research findings in this study are infodemic which occurred during the pandemic, also hit neighborhood association’s WAG 09 Dipowinatan. Two more years passed the Covid-19 Pandemic in Indonesia. The Indonesian people, especially the residents of neighborhood association 09 Dipowinatan, are taking a new order in dealing with Covid-19, including experiencing an infodemic. Infodemic occurs because of digital media and social media, which is very fast in disseminating information to receive the information quickly. The information regarding Covid-19 was no exception that the residents of neighborhood association 09 Dipowinatan received through the WhatsApp Group (WAG) Thus, digital literacy is needed for residents in dealing with this infodemic situation. This situation does not rule out that the information is disseminated, the information included in the disinformation group. However, this situation can anticipate with the digital literacy skills that residents must select and sort out the right information during the infodemic. State apparatus through the Head of neighborhood association / hamlet, and religious leaders in practice in neighborhood association’s WAG O9 can also be an alternative to mediating in situations if there is a debate in finding the truth regarding misinformation in WAG.